How the Blind Hear Colour. (March 2019) - Saysani, Armin
Crossmodal correspondences between seemingly independent sensory modalities are often observed in normal participants. For instance, colours commonly map consistently onto pure tones. In this study, we investigated colour-tone mapping in both normal trichromats and in people with congenital blindness. Participants were asked to match tones of differing pitch to named colours. In both cases, the tones selected varied consistently with the colour. The blind responses were similar to those of the trichromats, except in the case of red and green; the blind did not differentiate these colours, whereas the trichromats associated red with a higher tone and green with a lower tone. Otherwise, the results are consistent with a well-established association between pitch and lightness, with lighter colours associated with higher tones, and darker colours with lower tones. Because the blind never had any sensory experience of colour, their matching of colour to pitch is most likely based on semantic understanding.